Sediment Characteristics Study at Sharm Obhur, the Red Sea using Multibeam Backscatter - Hashem, Hatem; Shamji, V R (Journal of King Abdulaziz University: Marine Sciences, 2025)
Sharm Obhur, situated approximately 35 km north of Jeddah City along the Red Sea coast, is a prominent recreational area with diverse benthic habitats. Accurate mapping of seabed sediments is critical for characterizing marine ecosystems and elucidating benthic habitat distribution in this region. This study underscores the importance of assessing sediment distribution patterns in Sharm Obhur, particularly due to the prevalence of recreational activities and navigational traffic. This research investigates sediment dynamics in Sharm Obhur, a coastal creek near Jeddah, utilizing Multibeam Echo Sounder (MBES) backscatter data and grab sample analyses. The study focuses on understanding sediment distribution patterns and their implications for coastal management. MBES technology provides high-resolution data on seafloor composition and roughness, essential for assessing sediment types and bedforms. Through spatial alignment of MBES data with ground truth sediment samples, we analyze sediment characteristics and validate findings. Results indicate predominant sand presence with detectable mud in deeper channels and northern anthropogenically impacted areas. Gravel deposits correlate with coral formations near the creek edges. Tidal influence is evident, with increased sand presence at the creek entrance. The study demonstrates MBES backscatter's efficacy in mapping sediment distributions and seabed characteristics, benefiting marine science and coastal management. This research enhances knowledge of sediment transport processes, facilitating informed decision-making for sustainable coastal development and conservation efforts.